Humoral immune response against P2β from Trypanosoma cruzi in persons with chronic chagas disease: Its relationship with treatment against parasites and myocardial damage - Fabbro, Diana Lucrecia (2011)
We investigated the relationship between potentially pathogenic antibodies against a Trypanosoma cruzi ribosomal protein (P2β) and the evolution of Chagas disease and the effect of trypanocidal treatment on these variables. Seventy-eight patients with chronic Chagas disease who were followed-up for more than 20 years were divided into three groups: 30 asymptomatic persons undergoing specific treatment (group A), 37 asymptomatic persons not undergoing specific treatment (group B), and 11 patients with chronic chagasic cardiomyopathy (CCC) who were not treated. Five patients in group B showed evolution to myocardial abnormalities. Among persons with CCC, six showed no changes; the remaining persons showed progression of cardiac involvement. Levels of antibodies to P2β in persons in group A decreased from their initial values. This finding was not observed in persons in groups B and C. Comparisons at the end of the follow-up showed lower amounts of antibodies to P2β in groups A and C. These findings support the benefits of specific treatment during chronic infection.